Guatemala : Recent Economic Developments - Supplementary Information. (IMF Staff Country Reports; Country Report ;, 1998)
This paper describes economic developments in Guatemala during the 1990s. The paper discusses social and institutional expenditures of the peace program. The paper highlights that Guatemala's illiteracy rate was approximately 44 percent in 1995, the second highest in Latin America. Illiteracy is much higher in the predominantly rural departments (about 65 percent), where the indigenous population is more heavily concentrated, than in Guatemala City (16 percent) and is much higher for women (46 percent) than for men (33 percent). The paper also discusses the tax system and trade regime in Guatemala.